Efforts To Enhance Mental Health Among School-Aged Children During The Covid-19 Pandemic Through The Teacher And Parent Empowerment - Hidayah, Ridhoyanti; Nova, Renny; Sari, Efris Kartika (Journal of Innovation and Applied Technology, 2022)
School-aged children, as a developmental stage, are a group at high risk for mental health issues, particularly during this pandemic of COVID-19. Children may be perpetrators, witnesses, or victims of violence or irregularities perpetrated directly or through social media. This community service activity is designed to improve the mental health of children during the COVID-19 pandemic through early detection, prevention, and early treatment of mental health issues through parental and teacher empowerment programs. When children learn online and do more activities at home with their families, there are many factors that affect children's mental health. This is not widely known by the school, teachers, counselors, and parents clearly, which results in the state of the child getting worse. Through an empowerment program, they can discover early deviations that occur and take preventive measures with early treatment efforts during the COVID-19 pandemic.